SWIR absorption spectroscopy based on broad band source for the gas sensing - Barczak, Kamil; Olszewska, Aneta; Maciak, Erwin (Photonics Letters of Poland, 2024)
The paper presents research on short wavelength infrared (SWIR) absorption spectroscopy for gas sensing. The study focuses on detecting methane and ammonia, significant gaseous analytes, using a broadband light source and optical spectrum analyzer. The research demonstrates the potential for detecting methane and ammonia gas. The study addresses the current needs of industrial gas metrology and emphasizes the importance of detecting methane and ammonia due to their environmental and industrial implications. Full Text: PDF References S. Ziegler, R.C. Woodward, H.H.C. Iu, L.J. Borle, "Current Sensing Techniques: A Review", IEEE Sensors Journal, 9(4), 354 (2009). CrossRef Y. Qiao, J. Tao, C.H. Chen, J. Qiu, Y. Tian, X. Hong, J. Wu, "A Miniature On-Chip Methane Sensor Based on an Ultra-Low Loss Waveguide and a Micro-Ring Resonator Filter" Micromachines, 8(5), 160 (2017). CrossRef H. Yang, Xi. Bu, Y. Cao, Y. Song, "A methane telemetry sensor based on near-infrared laser absorption spectroscopy", Infrared Physics & Technology, 114, 103670 (2021). CrossRef